A game in yellow - Piper, Hailey (Saga Press, an imprint of Simon & Schuster, LLC, 2025)
"A kink-fixated couple, Carmen and Blanca, have been in a rut. That is until Blanca discovers the enigmatic Smoke in an under-street drug den, who holds pages to a strange play, The King in Yellow. Read too much, and you'll fall into madness. But read just a little and pull back, and it gives you the adrenaline rush of survivor's euphoria, leading Carmen to fall into a game of lust at a nightmare's edge. As the line blurs between the world Carmen knows and the one that she visits after reading from the play, she begins to desire more time in this other world no matter what horrors she brings back with her."--Amazon.